Detection and characterization of Coleus blumei viroid (CbVd) - Abdul Hamid, Siti Zaleha (2016)
Coleus blumei is an ornamental plant of the family Lamiaceae which originated from Indonesia and currently widely distributed worldwide. Coleus cultivar are popularly grown as garden plant and used for landscape. This ornamental can be infected by several viroids of the genus Coleviroid. Coleus blumei viroid (CbVd) is a viroid in family Pospiviroid which have been reported to cause disease in Coleus blumei worldwide. In Malaysia, sequences of CbVd-1 and CbVd-5 have been reported in Coleus species but more researches are needed to study the sequence variation and circularity of the RNA. The objectives of the study are to characterize CbVd from Coleus by using Reverse Transcription Polymerase Chain Reaction (RT-PCR) , to sequence and to prove the circularity of the RNA by Two Dimensional Polyacrylamide Gel (2D-PAGE). A total of 14 samples of Coleus with 11 samples showing no symptoms and 3 samples showing CbVd-like symptoms were collected around UPM. RT-PCR analysis of nucleic acid extracted from the Coleus samples showed that 6 out of the 14 Coleus blumei samples produced an amplicon of the expected size of range between 211 to 257 of CbVd. Sequencing of the amplicon confirmed the presence of Coleus blumei viroid 1 (CbVd-1) and Coleus blumei viroid 5 (CbVd-5) variants in positive samples. The study showed 96 to 99 % sequences similarity of positive samples with the reference; Coleus blumei viroid 1 (CbVd-1) (249nt) CbVd-K complete genome (Genbank: EU410620.1) and Coleus blumei viroid 1 (CbVd-1) CbVd-Chi complete genome (Genbank: DQ178399.1) with variants ranged from 211 to 240 nt. Positive samples also showed 84 to 91 % sequences similarity with Coleus blumei viroid 5 (CbVd-1) (274nt) clone 1, complete genome (Genbank : FJ151370.1) with variants range from 241 to 257 nt. The detected variants of CbVd-1 and CbVd-5 were from symptomatic and non-symptomatic Coleus sp. Meanwhile, 2D-PAGE produced negative results after few trials. Therefore, the circularity of the CbVd RNA cannot be confirmed in this study.